Shkatulkalite, a Rare Mineral from the Lovozero Massif, Kola Peninsula: A Re-Investigation - Andrey A. Zolotarev; Ekaterina A. Selivanova; Sergey V. Krivovichev; Yevgeny E. Savchenko; Taras L. Panikorovskii; Lyudmila M. Lyalina; Leonid A. Pautov; Victor N. Yakovenchuk (Minerals, 2018)
The crystal structure of shkatulkalite has been solved from the crystal from the Lovozero alkaline massif, Kola Peninsula, Russia. The mineral is monoclinic, P2/m, a = 5.4638(19), b = 7.161(3), c = 15.573(6) Å, β = 95.750(9)°, V = 606.3(4) Å3, R1 = 0.080 for 1551 unique observed reflections. The crystal structure is based upon the HOH blocks consisting of one octahedral (O) sheet sandwiched between two heteropolyhedral (H) sheets. The blocks are parallel to the (001) plane and are separated from each other by the interlayer space occupied by Na1 atoms and H2O groups. The Na2, Na3, and Ti sites are located within the O sheet. The general formula of shkatulkalite can be written as Na5(Nb1−xTix)2(Ti1−yMn2+y)[Si2O7]2O2(OH)2·nH2O, where x + y = 0.5 and x ≈ y ≈ 0.25 for the sample studied. Shkatulkalite belongs to the seidozerite supergroup and is a member of the lamprophyllite group. The species most closely related to shkatulkalite are vuonnemite and epistolite. The close structural relations and the reported observations of pseudomorphs of shkatulkalite after vuonnemite suggest that, at least in some environments, shkatulkalite may form as a transformation mineral species.